THEORETICAL MODELING OF ASSESSMENT OF PROFESSIONAL SKILLS OF ATHLETES - Kharitonova, A.I.; Klimova, E.M. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop a theoretical model for assessing the level of professional skills of athletes. Methods and structure of the study. On the basis of theoretical analysis, synthesis, expert evaluation and modeling, criteria, indicators, indicators for assessing the level of professional skill of athletes were identified, which made it possible to develop a theoretical model for assessing the level of professional skill of athletes, consisting of target, technological, procedural and resultant components. Results and conclusions. In the course of the theoretical analysis, it was determined that the professional skill of an athlete is an integral indicator that includes the highest level of mastered professional skills in the field of sports, efficiency and reliability, responsibility, emotional stability, special abilities, self-realization of an athlete and includes the highest qualification. Given these indicators, the theoretical model for assessing the professional skills of athletes includes the following components: target, technological, procedural and resultative.